THE IMPACT OF THE INFORMAL ECONOMY ON ECONOMIC DIVERSIFICATION IN ALGERIA - Djahmi , Merwan; Smaali , Faouzi (Journal of Excellence for Economics and Management Research, 2025)
This study explores the impact of the informal economy on economic diversification efforts in Algeria. Despite various government initiatives, the informal sector to grow, posing significant challenges to formalization, fiscal policy, and sustainable development. The research aims to diagnose the structure and dynamics of the informal economy, identify the factors driving its expansion, and assess its effects on diversification strategies. Using a qualitative analytical approach, the study draws on national and international data, official statistics, and previous literature. Findings reveal that the informal economy distorts market competition, undermines tax revenue, deters foreign investment, and perpetuates structural inefficiencies. Key drivers include excessive bureaucracy, high tax burdens, low regulatory quality, limited financial inclusion, and persistent unemployment. The study concludes that the informal economy acts both as a socio-economic buffer and a barrier to long-term reform. To mitigate its negative impact, the paper recommends a comprehensive strategy focusing on institutional reform, improved governance, targeted incentives, digitalization, and expanded social protection. These measures are essential to create an inclusive, competitive, and diversified Algerian economy.